Features of Mixing Slavic Languages (Ukrainian and Russian) with Hungarian in the Linguistic Landscape of the Transcarpathian Region - Shylov, Volodymyr (Slavia Centralis, 2024)
A large number of ethnic Hungarians live in the Transcarpathian region of Ukraine. They may cause the mixing of Slavic languages (Ukrainian and Russian) with Hungarian and vice versa. Examples of such mixings can be found on street inscriptions, so it makes sense to study this phenomenon as part of the analysis of the linguistic landscape. The cases presented in the article are supported by photographic material obtained by the author of this paper during his trips to Transcarpathia in 2019-2021. This topic may also be relevant for Slovenian-Hungarian and Serbian-Hungarian bilinguals from Prekmurje and Vojvodina.
Keywords: linguistic landscape, language mixing, Transcarpathia, Hungarian language, Ukrainian language, Russian language